Implementasi Flashcard Sebagai Media untuk Menambah Kosakata Bahasa Inggris pada Siswa SD Negeri 016 Kelurahan Sungai Perak - Puspitasari, Feni; Andriansyah, Agus; Riani Guspita, Anggi; Adha A Hakim, Assyaidil; Jaini; Zahra, Nabilah; Wahyudi (Indra Institute Research & Publication, 2022)
Vocabulary is a crucial thing that must be known as the main capital to learn sentence construction and other language skills because vocabulary is the basic foundation in language because one must have sufficient vocabulary to be able to understand what is read and heard, can speak and write in words. so that it can be understood by others. At SD Negeri 016 Sungai Perak Village, the majority of students were judged to lack a rich English vocabulary, the students also experienced difficulties in acquiring new vocabulary. To overcome this problem, the researcher chose one of the visual media that can help students in learning vocabulary, namely using flashcards or picture cards. The implementation method used in this study is in the form of observing English vocabulary, introducing flashcard media in teaching and learning activities, and implementing flashcard media in everyday life. This research was conducted with the aim that students are able to develop communication competencies and have an awareness of the nature and importance of English to improve the nation's competitiveness in a global society.